Fluorescent chemodosimeter for quantification of Cystathionine-y-synthase activity in plant extracts and imaging of endogenous biothiols - Agarwalla, Hridesh; Hoskere, Anila A.; Ali, Firoj; Pradhan, Swaraj Rashmi; Ganguly, Bishwajit; Pramanik, Sumit kumar; Das, Amitava (Chemical Communications, 2018)
A new reagent for quantification of CgS in plant extracts using a generalized methodology suitable for recognition of homocysteine (Hcy) with luminescence ON response.